Trends in developing metaheuristics, algorithms, and optimization approaches - Yin, Peng-Yeng, 1966- (Information Science Reference, 2013)
"This book provides insight on the latest advances and analysis of technologies in metaheuristics computing, offering widespread coverage on topics such as genetic algorithms, differential evolution, and ant colony optimization"--Vydavatelská anotace